Estigma e qualidade de vida das pessoas afetadas pela hanseníase - DINIZ, Shirley Priscila Martins Chagas (2023)
Leprosy, an infectious and contagious disease that mainly affects the skin and peripheral nerves, when not treated or diagnosed late, is capable of causing physical disabilities in addition to social and psychological repercussions that, in turn, contribute to a process of social exclusion and stigma directly affecting the quality of life of affected people. This study aimed to analyze the association between stigma and the quality of life of people affected by leprosy in the city of São Luís - MA. This is an analytical study, with a quantitative approach, inserted in a macroproject entitled “INTEGRAHANS MARANHÃO: an integrated approach to clinical, epidemiological (timeline), operational and psychosocial aspects of leprosy in a hyperendemic city in Maranhão”. The population consisted of patients diagnosed with leprosy, treated at the Itaqui Bacanga Sanitary District, notified in the Notifiable Diseases System (SINAN), during the years 2020 and 2022, who were in active registration, undergoing treatment for the disease for at least two months . The sample was given by convenience and consisted of 112 people. The study included people diagnosed with leprosy, aged 18 years or older, excluding those who did not show up for the appointment on the scheduled date. Data collection was carried out from October 2021 to December 2022. Instruments corresponding to the “INTEGRAHANS MARANHÃO” macroproject related to socioeconomic and demographic data, clinical profile, quality of life in dermatology “Dermatology Life Quality Index” (DLQI) and stigma scale “Explanatory Model Interview Catalog” (EMIC-AP). Among the 112 participants, the highest frequencies were male (58.0%), aged 41 to 51 years (23.2%), and 46.4% declared themselves brown. 62.5% were married/in a stable relationship. As for education, 32.1% had completed high school. 30.4% carried out some work activity on their own. 59.0% declared an average monthly income between 2 and 3 minimum wages and 79.5% stated that leprosy was a factor for changing income. 89.3% reported having regular/fixed housing and 75.9% denied having access to and registering for government assistance. As for the clinical characteristics of the disease, most participants (92.9%) were multibacillary and the borderline clinical form was predominant (63.4%). As for the degree of physical incapacity, the highest percentage was of Degree Zero (40.2%). 55.4% of respondents had no reactional episodes, and 54.5% had up to five injuries. The stigma related to leprosy was evidenced in the studied population and with regard to quality of life, 78% had some effect on quality of life, distributed as follows: 49.4% small effect, 26.4% moderate effect, 23.0% large effect and 1.2% very large effect. It was concluded that leprosy affected the quality of life of people undergoing treatment for the disease and that the stigma is still present. In this sense, the nursing professional has an important role in the adoption of strategies that help in the fight against the disease and assistance based on the demands presented by people affected by leprosy.